The Protection of Women and Children Post-Divorce in Sharia Courts in Aceh: A Sociological Perspective - Kasim, Fajri M; Nurdin, Abidin; Muthalib, Salman Abdul; Syarifuddin, Samsinar; Samad, Munawwarah (Universitas Islam Negeri Jakarta, 2022)
This study discusses the protection of women and children after divorce at the Syar'iyah Court in Aceh. A legal sociology approach is used to draw the decisions of the Banda Aceh, Aceh Besar, Pidie, Bireuen, and Lhokseumawe Syar'iyyah Courts. The interviews were conducted with judges, community leaders, village heads, heads of the Office of Religious Affairs (KUA), academics, traditional figures, and non-governmental organizations (NGO) activists. This study concludes that the Syar'iyah Court in Aceh, in its decision, has ensured the rights of women and children. The Syar'iyah Court in Aceh determined the provision of 'iddah, muṭ'ah maintenance, joint assets, and childcare rights to women. Children get living expenses, guardianship from the family, and care from the mother. Sociologically, the law has functioned as a means of social control through the Syar'iyah Court and judges as the main part of the legal structure supported by other elements of society so that the protection of women and children can be realized fairly.Keywords: protection of women and children; divorce; legal sociology; sharia court AbstrakKajian ini membahas perlindungan perempuan dan anak setelah perceraian pada Mahkamah Syar’iyah di Aceh. Dengan pendekatan sosiologi hukum, studi ini bersumber pada putusan-putusan Mahkamah Syar’iyyah Banda Aceh, Aceh Besar, Pidie, Bireuen, and Lhokseumawe dan wawancara kepada hakim, tokoh masyarakat, kepala desa, kepala Kantor Urusan Agama (KUA), akademisi, tokoh adat dan aktivis Lembaga Swadaya Masyarakat (LSM). Kajian ini menyimpulkan bahwa Mahkamah Syar’iyah di Aceh dalam putusannya telah memastikan hak-hak perempuan dan anak. Mahkamah Syar’iyah di Aceh menetapkan pemberian nafkah ‘iddah, nafkah muṭ‘ah, harta bersama dan hak pengasuhan anak kepada perempuan; dan anak mendapatkan biaya hidup, perwalian dari keluarga dan pengasuhan dari ibu. Secara sosiologis, hukum telah berfungsi sebagai alat kontrol sosial melalui Mahkamah Syar’iyah dan hakim sebagai bagian utama dari struktur hukum yang didukung oleh elemen masyarakat lainnya sehingga perlindungan terhadap perempuan dan anak dapat terwujud secara adil.Kata Kunci: perlindungan perempuan dan anak; perceraian; sosiologi hukum; Mahkamah Syar’iyah